The Effect of Product Quality and Brand Image on Customer Loyalty For Tuff Puff Products at Happy go Lucky Bandung - Anggita Nahwa Firdausi; Tuti Asmala (Takaza Innovatix Labs Ltd., 2026)
This study examines the effect of product quality and brand image on customer loyalty for Tuff Puff products at Happy Go Lucky Bandung amid rising local fashion competition. The research aims to analyze both partial and simultaneous influences of these variables. A quantitative method with a descriptive-verificative approach was employed. The population consisted of 5,697 visitors to Happy Go Lucky Bandung, and 98 respondents were selected using purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through classical assumption tests and multiple linear regression with SPSS 27. The results show that product quality and brand image each have a positive and significant effect on customer loyalty (t = 2.265, Sig = 0.026; t = 5.209, Sig = 0.000), and jointly have a significant influence (F = 77.361, Sig = 0.000) with an R² of 0.620. These findings indicate that improving product quality and a strong brand image significantly enhance customer loyalty. The conclusion emphasizes the need for consistent quality management and brand strengthening to sustain loyalty.